Achieving 20% Toluene-Processed Binary Organic Solar Cells via Secondary Regulation of Donor Aggregation in Sequential Processing - Wang, Yufei; Gao, Chuanlin; Lei, Wen; Yang, Tao; Liang, Zezhou; Sun, Kangbo; Zhao, Chaoyue; Chen, Lu; Zhu, Liangxiang; Zeng, Haoxuan; Sun, Xiaokang; He, Bin; et al. (Nano-Micro Letters, 2025)
Sequential processing (SqP) of the active layer offers independent optimization of the donor and acceptor with more targeted solvent design, which is considered the most promising strategy for achieving efficient organic solar cells (OSCs). In the SqP method, the favorable interpenetrating network seriously depends on the fine control of the bottom layer swelling. However, the choice of solvent(s) for both the donor and acceptor have been mostly based on a trial-and-error manner. A single solvent often cannot achieve sufficient yet not excessive swelling, which has long been a difficulty in the high efficient SqP OSCs. Herein, two new isomeric molecules are introduced to fine-tune the nucleation and crystallization dynamics that allows judicious control over the swelling of the bottom layer. The strong non-covalent interaction between the isomeric molecule and active materials provides an excellent driving force for optimize the swelling-process. Among them, the molecule with high dipole moment promotes earlier nucleation of the PM6 and provides extended time for crystallization during SqP, improving bulk morphology and vertical phase segregation. As a result, champion efficiencies of 17.38% and 20.00% (certified 19.70%) are achieved based on PM6/PYF-T-o (all-polymer) and PM6/BTP-eC9 devices casted by toluene solvent. Highlights: 1 Isomeric molecules are introduced to fine-tune the secondary nucleation process of the donor underlayer. 2 Binary organic solar cell processed with non-halogen solvent shows a champion efficiency of 20.0% (certified 19.7%). 3 Mechanism of the film formation processes and the sequential processing community about solvent design rules are proposed.